Utilização de copolímeros em bloco como scaffolds para a síntese de materiais inorgânicos com estrutura hierárquica de poros - Camila Silva Brey Gil (2017)
Hierarchical porous inorganic materials are of great interest for applications in catalysis, adsorption, separation, energy conversion and storage due to properties as high diffusion rates, high surface area and high pore volumes. In this work, it was demonstrated the preparation of hierarchical structures with ordered porosity from the self-assembly of block copolymers (BCPs). The scaffolds were synthesized using the SIM2PLE method that takes advantage of the spinodal decomposition induced in a block copolymer/extractable additive system (poly(styrene-b-ethylene oxide) / PEG 400). The influence of different parameters such as humidity, temperature, polymer blend composition and influence of vapors in the formation of hierarchical structures with ordered mesopores were evaluated. From the temperature variation different mesoporores morphology were obtained as the hexagonal type at 90 °C and the double diamond cubic morphology at 70 °C. These scaffolds were then used as hard templates for the synthesis of inorganic materials with hierarchical structure of pores based on the electroless deposition of nickel followed by the removal of the copolymer by different thermal treatments. This deposition was efficient on scaffolds with double diamond morphology and the deposition success attributed mainly to the three-dimensional interconnected pores characteristic of the double diamond morphology and absent in the hexagonal morphology. Inorganic materials with hierarchical structures such as nickel oxide and nickel metal were obtained from thermally treated samples under air and reducing atmosphere, respectively. The SAXS patterns indicated a transition from the double diamond morphology of the scaffolds to a single diamond morphology for the inorganic structures